2021
DOI: 10.1039/d1ra06718d
|View full text |Cite
|
Sign up to set email alerts
|

Na4PMo11VO40-catalyzed one-pot oxidative esterification of benzaldehyde with hydrogen peroxide

Abstract: The activity of the sodium salts of vanadium-doped phosphomolybdic acid was assessed in the oxidative esterification reaction of benzaldehyde with hydrogen peroxide in alkyl alcohol solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Keggin HPAs, such as the H 3 PMo 12 O 40 , can be converted to salts through different routes: (i) exchanging the protons with M x+ cations (i.e., M 3/x PMo 12 O 40 ) [18]; (ii) hydrolyzing the H 3 PMo 12 O 40 acid at pH = 4.5 with NaHCO 3 , which results in the removal of one MoO unit and provides a lacunar salt (i.e., Na 7 PMo 11 O 39 ) [19]; (iii) filling the vacancy of lacunar salt with an M x+ metal cation, giving a metal-substituted salt (i.e., Na 7−x PMo 11 MO 39 ) [20]; and (iv) replacing "n" Mo 6+ cations with "n" V 5+ ions, generating an acid with the general formula H 3+n PMo 12−n V n O 40 , which can be converted to any one of the salts previously cited (i.e., M 3+n Pmo 12−n V n O 40 , Na 7+n PMo 11−n V n O 39 , or Na 7+n−x PMo 11+n MV n O 39 ) [21]. Therefore, due to their bi-functional acidity (i.e., Lewis and Brønsted acidity), vanadiumsubstituted phosphomolybdate catalysts are potential candidates to be effective catalysts in acetalization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Keggin HPAs, such as the H 3 PMo 12 O 40 , can be converted to salts through different routes: (i) exchanging the protons with M x+ cations (i.e., M 3/x PMo 12 O 40 ) [18]; (ii) hydrolyzing the H 3 PMo 12 O 40 acid at pH = 4.5 with NaHCO 3 , which results in the removal of one MoO unit and provides a lacunar salt (i.e., Na 7 PMo 11 O 39 ) [19]; (iii) filling the vacancy of lacunar salt with an M x+ metal cation, giving a metal-substituted salt (i.e., Na 7−x PMo 11 MO 39 ) [20]; and (iv) replacing "n" Mo 6+ cations with "n" V 5+ ions, generating an acid with the general formula H 3+n PMo 12−n V n O 40 , which can be converted to any one of the salts previously cited (i.e., M 3+n Pmo 12−n V n O 40 , Na 7+n PMo 11−n V n O 39 , or Na 7+n−x PMo 11+n MV n O 39 ) [21]. Therefore, due to their bi-functional acidity (i.e., Lewis and Brønsted acidity), vanadiumsubstituted phosphomolybdate catalysts are potential candidates to be effective catalysts in acetalization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sodium salts of vanadium-doped phosphomolybdic acid were synthesized and evaluated in two distinct oxidation reactions with hydrogen peroxide: oxidative esterication of benzaldehyde, and oxidation of terpene alcohols. 58,59 In both processes, vanadium monosubstituted sodium phosphomolybdate salt was the most effective catalyst. In parallel work, we have found that pristine phosphomolybdic acid itself can efficiently catalyze the oxidation of nerol, allylic terpene alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic aldehydes and ketones are extremely useful synthetic precursors, as they can be modified into other functional groups easily through reduction, oxidation, cycloadditions, electrophilic substitution, Wittig reaction, and such others. 16 Till now, there is still example to perform the direct C–H functionalization at remote positions of such compounds. 17 It might be that the carbonyl group is too active to be compatible with the aminating reagent.…”
mentioning
confidence: 99%